Association between Health Information Obtained via Social Media and Eating Attitudes: A Descriptive and Correlational Study - Halil İbrahim Bilkay; Esra Ünal Çelik; Ayşenur Demir Küçükköseler (İstanbul Gelişim Üniversitesi Sağlık Bilimleri Dergisi, 2026)
Aim: Social media has become an important source of health information, shaping individuals’ eating attitudes and behaviours. This study aimed to investigate the potential relationship of seeking health information through social media and eating attitudes.Method: This descriptive and correlational study was conducted with 316 individuals aged 18 years and above through an online questionnaire. Data were collected using the Sociodemographic Information Form, the Eating Attitudes Test-26, and the Health Information Seeking and Verification Scale in Digital Media. Statistical analyses included descriptive statistics, correlation analysis, the Mann–Whitney U test, the Kruskal–Wallis test, and multiple linear regression analysis.Results: The findings indicated that women had higher disordered eating scores compared to men, and that increased dieting frequency was associated with more negative eating attitudes. A positive relationship was identified between the implementation of health-related content obtained from social media and eating attitudes, whereas digital verification behaviors were specifically associated with restrictive eating patterns. Regression analysis revealed that only gender and dieting frequency significantly predicted eating attitudes, while digital health information-seeking and the application of social media suggestions were not found to exert a direct significant effect.Conclusion: The findings suggest that individuals’ digital health information-seeking behaviors may exert indirect effects on their eating attitudes. Therefore, when evaluating eating attitudes, health professionals should consider gender, dieting behaviors, and digital media interactions. In addition, comprehensive interventions fostering media literacy and body image awareness should be developed.